ANALISIS PENGARUH IBU SEBAGAI CONSUMER SOCIALIAZATION AGENT PADA KEPUTUSAN PEMBELIAN OLEH KONSUMEN REMAJA - Rena Feri Wijayanti; Tri Yulistyawati Evelina; Joni Dwi Pribadi (Adbis: Jurnal Administrasi dan Bisnis, 2017)
Consumer behavior is formed through various processes that have been passed since the early age. The initial process that contributes greatly in the formation of consumer behavior is at the stage of socialization conducted by an individual in the family environment. The family becomes the starting place of learning is done in addition to the influence of the surrounding environment or peers. Adolescence is one category of consumer age that has the potential to be the target consumers. Based on the socialization process experienced by adolescents it will be seen how their behavior becomes a consumer who can make decisions in making purchases.